2018
DOI: 10.2147/ott.s169880
|View full text |Cite|
|
Sign up to set email alerts
|

PLK1 as a potential prognostic marker of gastric cancer through MEK-ERK pathway on PDTX models

Abstract: BackgroundPLK1 has been identified as having a great effect on cell division and maintaining genomic stability in mitosis, spindle assembly, and DNA damage response by current studies.Materials and methodsWe assessed PLK1 expression in cervical cancer tissues and cells. We have also evaluated the effects of PLK1 on gastric cancer cell proliferation, migration, and apoptosis both in vitro and in vivo.ResultsOur results show that PLK1 is overexpressed in gastric cancer tissues and cells. Inhibition of PLK1 contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…PLK1 was reported to promote the abnormalities of early cervical columnar epithelial cells ( Oh et al, 2014 ; Yang et al, 2017 ). The overexpression of PLK1 was found in various types of cancers and was associated with poor prognosis of cancer patients ( Weng Ng et al, 2016 ; Lin et al, 2017 ; Li et al, 2017 ; Dang et al, 2018 ). Although several researches involved PLK1 in cervical cancer ( Yang et al, 2017 ; Li et al, 2011 ; Zhang et al, 2009 ; Gao et al, 2006 ; Zuco et al, 2015 ; Chhavi et al, 2010 ), PLK1 expression in cervical cancer was detected with single methods and small samples by those studies.…”
Section: Introductionmentioning
confidence: 99%
“…PLK1 was reported to promote the abnormalities of early cervical columnar epithelial cells ( Oh et al, 2014 ; Yang et al, 2017 ). The overexpression of PLK1 was found in various types of cancers and was associated with poor prognosis of cancer patients ( Weng Ng et al, 2016 ; Lin et al, 2017 ; Li et al, 2017 ; Dang et al, 2018 ). Although several researches involved PLK1 in cervical cancer ( Yang et al, 2017 ; Li et al, 2011 ; Zhang et al, 2009 ; Gao et al, 2006 ; Zuco et al, 2015 ; Chhavi et al, 2010 ), PLK1 expression in cervical cancer was detected with single methods and small samples by those studies.…”
Section: Introductionmentioning
confidence: 99%
“…PLK1 overexpression is regarded as a marker for poor prognosis in a number of types of cancer, and PLK1 has become an attractive target for anticancer therapy over the past several years ( 19 ). Studies have demonstrated that PLK1 is overexpressed in a variety of cancers, and that it regulates proliferation, migration and apoptosis on various cancer types, such as gastric cancer ( 35 ), non-small cell lung cancer ( 36 ) and pancreatic cancer ( 37 ). Moreover, it has been suggested that PLK1 silencing may lead to cell cycle arrest and apoptosis in AML ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Preceding studies have illustrated that overexpressed PLK1 is correlated with poor survival rate in numerous types of cancers as breast, melanoma, and non-small cell lung cancer. 8 Indeed, PLK1 inhibition makes cells unable to complete mitosis, finally resulting in cell death, 9,10 suggesting that PLK1 may be a powerful therapeutic target for cancer control. [11][12][13] Volasertib (Vola) is a selective and powerful cell cycle kinase inhibitor that prompts mitotic arrest and apoptosis by targeting PLK1.…”
Section: Introductionmentioning
confidence: 99%